Role of mitochondria-bound HK2 in rheumatoid arthritis fibroblast-like synoviocytes - Torres, Alyssa; Kang, Sarah; Mahony, Christopher B.; Cedeño, Martha; Oliveira, Patricia G.; Fernandez-Bustamante, Marta; Kemble, Samuel; Laragione, Teresina; Gulko, Percio S.; Croft, Adam P.; Sanchez-Lopez, Elsa; Miyamoto, Shigeki; et al. (Frontiers in Immunology, 2023)
Background Glucose metabolism, specifically, hexokinase 2 (HK2), has a critical role in rheumatoid arthritis (RA) fibroblast-like synoviocyte (FLS) phenotype. HK2 localizes not only in the cytosol but also in the mitochondria, where it protects mitochondria against stress. We hypothesize that mitochondria-bound HK2 is a key regulator of RA FLS phenotype. Methods HK2 localization was evaluated by confocal microscopy after FLS stimulation. RA FLSs were infected with Green fluorescent protein (GFP), full-length (FL)–HK2, or HK2 lacking its mitochondrial binding motif (HK2ΔN) expressing adenovirus (Ad). RA FLS was also incubated with methyl jasmonate (MJ; 2.5 mM), tofacitinib (1 µM), or methotrexate (1 µM). RA FLS was tested for migration and invasion and gene expression. Gene associations with HK2 expression were identified by examining single-cell RNA sequencing (scRNA-seq) data from murine models of arthritis. Mice were injected with K/BxN serum and given MJ. Ad-FLHK2 or Ad-HK2ΔN was injected into the knee of wild-type mice. Results Cobalt chloride (CoCl2) and platelet-derived growth factor (PDGF) stimulation induced HK2 mitochondrial translocation. Overexpression of the HK2 mutant and MJ incubation reversed the invasive and migrative phenotype induced by FL-HK2 after PDGF stimulation, and MJ also decreased the expression of C-X-C Motif Chemokine Ligand 1 (CXCL1) and Collagen Type I Alpha 1 Chain (COL1A1). Of interest, tofacitinib but not methotrexate had an effect on HK2 dissociation from the mitochondria. In murine models, MJ treatment significantly decreased arthritis severity, whereas HK2FL was able to induce synovial hypertrophy as opposed to HK2ΔN. Conclusion Our results suggest that mitochondrial HK2 regulates the aggressive phenotype of RA FLS. New therapeutic approaches to dissociate HK2 from mitochondria offer a safer approach than global glycolysis inhibition.